EPC Agenda 2004-11-11 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Consent item moved to business. Agenda Approved. Minutes of 8/30/18 – Approved. Provost Report. Faculty Eligible for Emeritus Status Approved. Robert's Rules of Order presentation. Vice Chair Report. Vice President of Administration and Finance Report. Associated Students Report. Statewide Senator Report. Staff Report. APARC Report. EPC Report. Graduate Studies Surveys Report. FSAC Report. SAC Report. CFA Report.